Effectiveness of Kangaroo Mother Care in Early Weaning of Oxygen Therapy among Preterm Neonates in a Tertiary Care Center in Nepal: A Quasi-Experimental Study - Karki, Rajani; Basnet, Sudha; Gupta, Pradeep Kumar; Thapa, June; Adhikari, Punam; Shah, Prakash Man (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Kangaroo Mother Care is a cost-effective intervention based on skin-to-skin contact and exclusive breastfeeding that improves survival in preterm and low birth weight infants. Early initiation of Kangaroo Mother Care during respiratory support has shown benefits in stabilizing vital parameters and improving oxygenation. The aim of this study was to find out the effectiveness of early Kangaroo Mother Care during oxygen therapy in preterm neonates. Methods: This was a quasi-experimental study conducted among 62 preterm neonates of less than 37 weeks of gestation who were on assisted respiratory support, admitted in neonatal ward and neonatal intensive care unit of Tribhuvan University Teaching Hospital from May 2023 to March 2024. Ethical approval was obtained from the Institutional Review Board of the Institute of Medicine (Reference no: 545(6-11) E2). The enrolled neonates were alternately assigned to the two groups interventional and conventional care group. Neonates in intervention group were started on KMC while still receiving oxygen therapy while the conventional care group received daily routine care. Data was collected in predesigned performa and was entered in Statistical Package for the Social Sciences version 26. Results: The duration of oxygen therapy was shorter in the Kangaroo Mother Care group than in the conventional group, with a mean difference of 29.30 h (95% CI 45.98 to 12.62; p=0.001). Hospital stay was shorter in the same group (6.47± 2.84 vs 7.55±3.74 days; p=0.215). Complications were also less frequent, and vital parameters improved significantly after one hour of Kangaroo Mother Care. Conclusions: Early Kangaroo Mother Care during oxygen therapy reduces duration of oxygen therapy, hospital stay and neonatal complications along with stabilization of vital parameters.